1999
DOI: 10.1097/00004872-199917090-00003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of erythropoietin on interleukin-1β mediated increase in nitric oxide synthesis in vascular smooth muscle cells

Abstract: rHuEPO inhibits IL-1beta induced NO production by suppressing iNOS mRNA and protein expressions through EpoR, and the PLC-gamma1 and PKC pathway may be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…In cultured endothelial cells, recombinant Epo may reduce expression of eNOS, whereas in vascular smooth muscle cells Epo raises the cytosolic calcium content of vascular smooth muscle cells by stimulation of protein kinase C and phospholipase C␥1 (2,43,46). However, in these studies, the concentrations of Epo used (20 -250 U/ml) greatly exceeded concentrations observed in plasma after adenoviral-mediated gene transfer of recombinant Epo in our study (ϳ5 U/ml; Table 1).…”
Section: Discussioncontrasting
confidence: 62%
“…In cultured endothelial cells, recombinant Epo may reduce expression of eNOS, whereas in vascular smooth muscle cells Epo raises the cytosolic calcium content of vascular smooth muscle cells by stimulation of protein kinase C and phospholipase C␥1 (2,43,46). However, in these studies, the concentrations of Epo used (20 -250 U/ml) greatly exceeded concentrations observed in plasma after adenoviral-mediated gene transfer of recombinant Epo in our study (ϳ5 U/ml; Table 1).…”
Section: Discussioncontrasting
confidence: 62%
“…Subsequently, a number of published studies have documented biological effects of EPO on vascular smooth muscle and endothelial cells. 8,[34][35][36][37] In all of these in vitro studies the concentrations of EPO used range from 4 to 250 U/ml. 6,8,31,37 While the physiological concentrations of EPO in most healthy animals and humans are in the range of 4-30 mU/ml, up to 100-fold increases can be seen in severe anemias (thus resulting in plasma concentrations as high as 3 U/ml).…”
Section: Discussionmentioning
confidence: 99%
“…8,[34][35][36][37] In all of these in vitro studies the concentrations of EPO used range from 4 to 250 U/ml. 6,8,31,37 While the physiological concentrations of EPO in most healthy animals and humans are in the range of 4-30 mU/ml, up to 100-fold increases can be seen in severe anemias (thus resulting in plasma concentrations as high as 3 U/ml). 36,38 Furthermore, relatively high EPO plasma concentrations in the order of 1-5 U/ml may be obtained intermittently in patients immediately after intravenous injection of the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EPO can decrease the plasma iron concentration and increase the ability of plasma to inhibit lipid peroxidation [79,80]. The inhibitory effect of EPO on iNOS has been shown to require the activation of the phospholipase Cγ1 and protein kinase C pathway [81].…”
Section: Antioxidant Properties Of Epo During Ali/ardsmentioning
confidence: 99%